ANALISIS PENGARUH PENALARAN ETIS DAN SENSITIVITAS ETIKA TERHADAP PERILAKU ETIS MAHASISWA - Anggriati, Lia; M, Muslichah (Fakultas Ekonomi, Universitas Cenderawasih, 2019)
Along with the violations of ethics that occur frequently committed by accountants, both publicaccountants, and internal company accountants and government accountants and based on the resultsof research that has been done before producing different results, this study aims to examine the effectof ethical reasoning and ethical sensitivity to behavior ethical students. The population in this studywere accounting students at STIE Malangkucecwara. Research samples were taken using a simple randomsampling technique. The total sample used in the study was 184 accounting students. This study usesthe Partial Least Square (PLS) method. The results of this study indicate that (1) Ethical sensitivityhas a significant positive effect on ethical behavior. (2) Ethical sensitivity has a significant positiveeffect on ethical reasoning. (3) Ethical reasoning has a significant positive effect on ethical behavior.(4) Ethical reasoning does not mediate the relationship between ethical sensitivity on ethicalbehavior.